Analysis of the Effect of Financial Literacy, QRIS Usage, and Financial Attitude on Personal Financial Management Behavior with Lifestyle as a Moderating Variable in Pontianak - Windy Ananda Pratiwi; Edy Suryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effect of financial literacy, QRIS usage, and financial attitude on personal financial management behavior, with lifestyle as a moderating variable, among QRIS users in Pontianak City. The study employed a quantitative associative design using primary data collected through a structured questionnaire distributed via Google Form. A total of 150 respondents were selected using purposive sampling, and the sample size was determined using the Cochran formula. Data were analyzed using instrument tests (validity and reliability), classical assumption tests, and Moderated Regression Analysis (MRA). The results indicate that financial attitude has a positive and significant effect on personal financial management behavior, while QRIS usage shows a significant negative effect. Lifestyle significantly influences financial management behavior and moderates the relationship between financial attitude and financial management behavior. However, lifestyle does not moderate the effects of financial literacy and QRIS usage. These findings suggest that strengthening financial attitude and controlling spending behavior in digital transactions are essential to improve personal financial management in the era of QR-based payments.